Optimization of SPR signals: Monitoring the physical structures and refractive indices of prisms - Mukhtar, WM; Halim, RM; Hassan, H (E D P SCIENCES, 2024)
Surface plasmon resonance (SPR) can only be achieved if sufficient energy is provided at the boundary between metal and dielectric. An employment of prism as a light coupler by using Kretschmann configuration is one of the alternative for the production of adequate energy to be generated as surface plasmon polaritons (SPP). This work is carried out to investigate the effect of physical structure of the prism and its refractive index to the excitation of SPPs. A 50nm gold thin metal film with dielectric constant of e=-12.45i+1.3 was deposited on the hypotenuse surface of the prisms. The physical structures of the prisms were varied such as triangular, conical, hemispherical and half cylindrical. These prisms were classified into two types of refractive indices (RI), namely n = 1.51(type BK7) and n = 1.77(type SF11). Based on SPR curve analyses, we discovered that strong SPR signals which consist of 82.98% photons were excited as SPPs can be obtained by using type-BK7 prism with physical structures of hemispherical or half cylindrical. From the view of selectivity ability as sensors, the usage of type-SF11 prisms (half cylindrical and hemispherical) able to enhance this impressive feature in which sharp SPR curves with small FWHM values were obtained. In conclusion, apart from properties of thin film materials, the physical structure of prisms and their RI values play crucial roles to obtain optimum SPR signal. High sensitivity SPR sensor can be established with the appointment of type-BK7 prisms (hemispherical or half cylindrical shape) as light couplers.